2018
DOI: 10.1021/acs.jafc.8b04303
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Interaction between Angiotensin-Converting Enzyme (ACE) and ACE Inhibitory Peptide from Saurida elongata

Abstract: Angiotensin-converting enzyme (ACE) inhibitory peptides derived from food protein exhibited antihypertensive effects by inhibiting ACE activity. In this work, the interaction between ACE inhibitory peptide GMKCAF (GF-6) and ACE was studied by isothermal titration calorimetry (ITC), molecular docking, ultraviolet absorption spectroscopy, fluorescence spectroscopy, and circular dichroism spectroscopy. Experimental results revealed that the binding of GF-6 to ACE was a spontaneous exothermic process driven by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 43 publications
2
20
1
Order By: Relevance
“…The molecular docking study revealed that NIFRPF formed hydrogen bonds with the S1 pocket (Ala 354, Glu 384 and Tyr 523) and established direct interaction with Zn (II), which could explain its inhibition effect against ACE activity. However, previous research showed that some ACE inhibitory peptides, such as QAGLSPVR and GMKCAF, based on a non‐competitive inhibition mechanism, could not interact with the active site of ACE 39, 40 . Therefore, it might be reasonable that peptides FHPFPR and NWFPLPR did not interact with main active sites of ACE in the current study.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The molecular docking study revealed that NIFRPF formed hydrogen bonds with the S1 pocket (Ala 354, Glu 384 and Tyr 523) and established direct interaction with Zn (II), which could explain its inhibition effect against ACE activity. However, previous research showed that some ACE inhibitory peptides, such as QAGLSPVR and GMKCAF, based on a non‐competitive inhibition mechanism, could not interact with the active site of ACE 39, 40 . Therefore, it might be reasonable that peptides FHPFPR and NWFPLPR did not interact with main active sites of ACE in the current study.…”
Section: Resultsmentioning
confidence: 69%
“…However, previous research showed that some ACE inhibitory peptides, such as QAGLSPVR and GMKCAF, based on a non-competitive inhibition mechanism, could not interact with the active site of ACE. 39,40 Therefore, it might be reasonable that peptides FHPFPR and NWFPLPR did not interact with main active sites of ACE in the current study.…”
Section: Novel Ace Inhibitory Peptides and Molecular Dockingmentioning
confidence: 76%
“…Compared with microorganism fermentation and chemical degradation processes, proteolytic hydrolysis method has been widely used because of its advantages of easy control, environmental friendliness, no residual chemical reagents, or no harmful substances (20,57,58). The biological activities of protein hydrolysates are closely contacted with the biopeptide composition, and specificity of enzymes is the key factor affecting those properties (59,60).…”
Section: Preparation Of Milt Protein Hydrolysatementioning
confidence: 99%
“…Usually, the ACE inhibitory peptide functions by directly binding to ACE. The interaction between ACE and peptides was demonstrated in kinetic studies and molecular docking simulations. …”
Section: Introductionmentioning
confidence: 99%